2012
DOI: 10.1128/aac.01127-12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Xylitol To Enhance the Therapeutic Efficacy of Polymethylmethacrylate-Based Antibiotic Therapy in Treatment of Chronic Osteomyelitis

Abstract: e Using a rabbit model of postsurgical osteomyelitis, we demonstrate that incorporation of xylitol into polymethylmethacrylate (PMMA) bone cement enhances the elution of daptomycin under in vivo conditions. We also demonstrate that this can be correlated with an improved therapeutic outcome in the treatment of a chronic bone infection following surgical debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
3
28
0
1
Order By: Relevance
“…Xylitol has been used on a large scale by dental, food and medical and pharmaceutical industries. In addition, it has shown activity against biofilms in wounds (5) and has been tested in animal models as a complementary measure in the treatment of osteomyelitis (6) . Its activity against strains of Pseudomonas aeruginosa and Staphylococcus aureus (5) is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Xylitol has been used on a large scale by dental, food and medical and pharmaceutical industries. In addition, it has shown activity against biofilms in wounds (5) and has been tested in animal models as a complementary measure in the treatment of osteomyelitis (6) . Its activity against strains of Pseudomonas aeruginosa and Staphylococcus aureus (5) is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Algeria showed that, the expansion of basic oil leaves in broth culture immunised with S. aureus and E. coli [6], of which 300 are financially imperative in scent advertise. Basic oils are Complex mixers including many single mixes.…”
Section: Discussionmentioning
confidence: 99%
“…They can be gotten by expression, maturation or extraction yet the technique for steam refining is most normally utilised for business creation. An expected 3000 fundamental oils are known [6], of which 300 are financially imperative in scent advertise. Basic oils are Complex mixers including many single mixes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is not clear if the concentrations used in our study can be achieved at the site of infection when antibiotics are administered systemically. However, antibiotics are also often administered locally using some form of matrix-based delivery system, particularly in orthopedic medicine (11,(23)(24)(25). We also recently described a novel nanocage-based system for the targeted local delivery of daptomycin (26).…”
Section: Figmentioning
confidence: 99%